Pemberdayaan Stakeholder dalam Manajemen Berbasis Sekolah sebagai Strategi Peningkatan Mutu Madrasah - hidayatul Kusnadi Wijaya; Riska Putri; M. Arifin Ilham; Aprizal Ahmad; Rully Hidayatullah (CV. ITTC INDONESIA, 2026)
School-Based Management has become a strategic approach to improving the quality of education through granting broader authority to schools or madrasahs in managing resources independently, participatively, and accountably. However, the implementation of School-Based Management in various madrasahs still faces challenges, particularly the limited involvement of stakeholders in decision-making processes and educational quality development. This article aims to analyze the importance of stakeholder empowerment in supporting the successful implementation of School-Based Management as a strategy for improving madrasah quality. This study employed a literature review method by examining various scientific sources, including books, journal articles, and relevant educational policy documents. The findings indicate that the active involvement of principals, teachers, students, parents, school committees, and the community can strengthen the effectiveness of madrasah management, improve the quality of learning, encourage a participatory culture, and reinforce institutional transparency and accountability. Furthermore, stakeholder empowerment contributes to the creation of a conducive learning environment that supports sustainable quality improvement. Therefore, optimizing the role of stakeholders is an essential factor in establishing effective, adaptive, and high-quality madrasah governance.